Analysis of the effect of the use of multimedia tools (Journal of Management and Business Education, 2018)
The need to adapt university education to the new teaching-learning processes demanded by students, teachers and educational institutions leads us to think deeply about the subject. In this sense, the Internet and the use of smartphones in the classroom allow to use active and motivational methodologies to the students. This study examines the effect that causes the use of different digital tools in students such as Socrative or Bolsa Virtual and audiovisual elements in two subjects of the Administration and Management degree by comparing them in the academic year 2017/2018. The aim of this paper is fourfold: firstly, to measure and assess the results obtained in terms of improvements in students' knowledge and skills. Secondly, to analyse and determine to what extent the use of digital applications enables us to achieve a higher motivation in the classroom. Thirdly, to ascertain whether there are any differences between the results obtained in each of the tools employed. Finally, analyse if there are differences between the results obtained between the two subjects with different number of students and of different courses.
Keywords: Motivation; digital tools; smartphone; higher education; active learning